Developing twenty-first century skills: insights from an intensive interdisciplinary workshop Mosaic of Life - Milosevic, Tamara (Approaching religion, 2013)
The Baltic Sea, one of the world’s largest semi-enclosed seas, which, with its very low salinity and quasi-isolation from the big oceans cannot decide whether it is a sea or a large lake. This geologically-unique environment supports an even more surprising and delicate marine ecosystem, where a complex community of fishes, marine mammals and important microscopic organisms creates a magical mosaic of life. Humans have enjoyed the abundance of life in the Baltic Sea for thousands of years, and major Scandinavian and Baltic cities have oriented themselves towards this geo-ecosystem in order to develop and seek ecological, economical and cultural inspiration and wealth. The ‘Mosaic of Life’ workshop aimed at going beyond the obvious in examining the meaning of the Baltic Sea by gathering together a selection of young, creative minds from different backgrounds ranging from the arts and economics to geology and life sciences. This intensive workshop was designed as a unique training opportunity to develop essential twenty-first century skills - to introduce and develop creative, critical and interdisciplinary thinking and collaborative teamwork, as well as to foster a visual and scientific literacy, using project-based learning and hands-on activities. Our final goal has been to be inspired by the resulting connections, differences and unifying concepts, creating innovative, interdisciplinary projects which would look further than the sea - further than the eye can see and further into the future.